Impact of residual ridge anatomy on masticatory efficiency of conventional complete denture users - CAMPOS,Maria de Fátima Trindade Pinto (2021)
ABSTRACT Objective: The aim of this cross-sectional study was to evaluate the anatomical characteristics of edentulous residual ridges in stone casts of complete dentures users and assess correlations with masticatory efficiency. Methods: The sample included 74 study casts, of which 37 were higher and 37 bottom. Measurements were performed using a drypoint compass and a transparent ruler. Arches and ridges of maxillae and mandibles were classified into small, medium, and large. Masticatory efficiency was obtained by the sieve method with the old prostheses and 3 months after placement of new prostheses. The correlations between the anatomical variables of the ridges and arches (height, width and size) and masticatory efficiency were verified by the Spearman correlation test. Significant differences in masticatory efficiencies were assessed by the Wilcoxon test. Results: People with larger maxillary alveolar ridge presented better masticatory performance with old and new dentures. There was no correlation between maxillary ridge width and size with masticatory efficiency, but a correlation was found between maxillary arch width and masticatory efficiency evaluated with the old dentures. Conclusions: With the new dentures, the correlation had a tendency for significance. For the mandible, no correlation was found between height, width, and size of the ridge or with width, length, and size of the arch and masticatory efficiency. In addition, there was no significant difference between masticatory efficiencies evaluated with the old and new prostheses. For the maxilla, ridge height and arch width influence masticatory efficiency. For the mandible, the anatomy had little influence on masticatory performance.